Laser Technology and its Applications - Yufei Ma (IntechOpen, 2019)
The laser has become more and more important in scientific research and industrial applications. Now, the laser wavelength can cover the range from ultraviolet to terahertz and output laser performance has significantly progressed in recent years. This book is focused on the advanced diode laser, fiber laser, and their applications in laser ablation, laser-introduced fluorescence, and laser treatment. The advantages of laser technology are shown comprehensively.
English
Keywords: Physical Sciences; Engineering and Technology; Laser Physics; Physics